Integrating Enterprise Risk Management (ERM) and Environmental, Social, and Governance (ESG) Risks into Balanced Scorecard (BSC) for Sustainable Performance in a Rural Bank - Ni Putu Gita Rahmaniati; Perminas Pangeran (Bina Nusantara University, 2025)
The research explored how the integration as Enterprise Risk Management (ERM) based on ISO 31000 with Environmental, Social, and Governance (ESG) risk considerations into a Balanced Scorecard (BSC) framework could enhance sustainable financial performance in small financial institutions. A single-case study was conducted on Rural Bank, PT BPR “C”, while primary and secondary data were collected through questionnaires, interviews, and company documents. Risks were identified, analyzed, evaluated, and addressed in accordance with ISO 31000 principles, while ESG factors were embedded in the strategic mapping of BSC perspectives. The results reveal that environmental risks exert the most significant impact on financial outcomes, notably influencing key indicators such as Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), and Return on Assets (ROA). They highlight the urgent need for proactive risk mitigation strategies. By mapping risks to strategic objectives, the institution improves transparency, resilience, and alignment between risk management and performance measurement. The findings support extending the Resource-Based View (RBV) and Stakeholder theory, demonstrating that internal capabilities and stakeholder-focused governance can serve as critical drivers of competitive advantage and long-term value creation. The research offers practical contributions by presenting a replicable model that enable rural banks to integrate ESG risk management into their operational and strategic frameworks. However, as a single-case study reliant on selfreported measures, the findings are limited in generalizability. Future research should explore longitudinal impacts and cross-institutional applications to validate and refine the integrated ERM-ESG-BSC framework proposed.